Maternal satisfaction with breastfeeding in the first month postpartum and associated factors - Andrea Francis Kroll de Senna; Camila Giugliani; Juliana Avilla; Agnes Meire Branco Leria Bizon; Ana Cláudia Magnus Martins; Elsa Regina Justo Giugliani (BMC, 2020)
Abstract Background Breastfeeding success has been measured based on its duration, disregarding satisfaction with the maternal experience. Studies to investigate maternal satisfaction with breastfeeding are rare, especially in Brazil, and little is known about their determinants. The aim of this study was to measure the level of satisfaction with breastfeeding in a group of women in the first month of their child's life, and to identify factors associated with higher maternal satisfaction. Methods A cross-sectional study nested within a cohort was conducted with 287 women recruited at two (one public, one private) maternity services in the city of Porto Alegre, southern Brazil, from January to July 2016. Women residing in the municipality who had given birth to a healthy singleton born at term, were rooming in, and had initiated breastfeeding were randomly included. During the week after the child was 30 days old, women were interviewed at their homes to measure the level of maternal satisfaction with breastfeeding, using the Maternal Breastfeeding Evaluation Scale (MBFES), validated for use in the Brazilian population. Associations between maternal satisfaction and explanatory variables were estimated using multivariate Poisson regression with robust variance in a four-level hierarchical approach. Satisfaction level was categorized using as cutoff point the median score obtained with the MBFES. Women with scores equal to or above the median were considered to have higher levels of satisfaction, whereas those scoring below the median were considered to be less satisfied. Results Maternal satisfaction with breastfeeding in the first month postpartum was high, with a median score of 124 on MBFES, close to the maximum score (145 points). The prevalence of more elevated levels of satisfaction with breastfeeding was higher among women with brown (pardo) and black skin color (prevalence ratio [PR] 1.33, 95%CI 1.05;1.69), those who lived with the partner (PR 1.75, 95%CI 1.05;2.94), who planned to breastfeed for 12 months or more (PR 1.48, 95%CI 1.02;2.17), and who did not report low milk supply (PR 1.47, 95%CI 1.03;2.10) or cracked nipples (PR 1.29, 95%CI 1.01;1.65). Conclusions The factors associated with maternal satisfaction with breastfeeding in the first month postpartum include individual factors and maternal expectations, family constitution, as well as breastfeeding-related problems.